The Unique Amphipoda and Tanaidacea (Crustacea: Peracarida) Associated With the Brown Algae Dictyota sp. From the Oceanic Trindade Island, Southwestern Atlantic, With Biogeographic and Phylogenetic Insights - Iwasa-Arai, Tammy; Siqueira, Silvana G. L.; Segadilha, Juliana L.; Leite, Fosca P. P. (Frontiers in Marine Science, 2021)
Oceanic islands are known by their unique evolutionary histories and high endemicity caused by isolation. The island of Trindade is located about 1160 km from the Brazilian coast, in the tropical southwestern Atlantic. This is the first survey on the biodiversity of Peracarida from Trindade Island, with the first reports of Tanaidacea from the island and the description of Synapseudes isis sp. nov., and three new species of Amphipoda (Ampithoe thaix sp. nov., Elasmopus gabrieli sp. nov. and Eusiroides lucai sp. nov.). This is the first record of Eusiroides from Brazil. We also comment of the phylogenetic relationships of Synapseudes based on morphological characters and its biogeography, through the Bayesian Binary MCMC analysis (BBM), which suggested an Indo-Pacific origin of the genus. Finally, we compare the biodiversity of Trindade Island with the Abrolhos Archipelago, the closest islands from the coast in the continental shelf, and our results suggest a high endemicity of Peracarida, corresponding to 44% of Amphipoda and 50% of Tanaidacea species in the island of Trindade.